The chemical composition of ice and water under ice of Lake Onega (the case of Petrozavodsk Bay) - A. V. Sabylina; T. A. Efremova (Лëд и снег)
Data on the content of ions, nutrients and organic substance in snow on the ice as well as in the ice and water under ice in the Petrozavodsk Bay and Central part of Onega Lake (March 2017) as well as in the snow cover on the Petrozavodsk Bay shore (2008–2017) are presented. In areas of the Petrozavodsk Bay experiencing anthropogenic and natural impacts, chloride ions prevail among anions in crystallo-hydrates, while sulphate ions are prevalent at the exit from the Bay and in the central part of the lake (clean water). The water under ice has a bicarbonate-calcium composition. Among the inorganic forms of nitrogen compounds (NH4+, NO2, NO3) ammonium ions prevail in the ice(70%), while in snow and the water under ice the prevalent are nitrate ions and organic nitrogen. The content of nitrogen compounds and mineral and total phosphorus is increased in the upper layer of ice. Note, that chemical composition of ice cover is formed by both, a water under the ice and atmospheric precipitation. To determine intensity of involvement of dissolved substances to the ice in combination with ice-forming water, the coefficient of involvement Kv was used. As is shown by our studies, value of the involvement index Kv is individual for each chemical component, however a certain general regularity is observed. Thus, the not proportional relations between contents of ammonium and phosphate ions in ice and water under ice were noticed. The increased involvement indices of NH4+and РО43− into the ice from the water under ice seem to be due to the high rate of migration of these ions together with detachment of them from organic matter molecules.